Physiological ecology of Methanobrevibacter cuticularis sp. nov. and Methanobrevibacter curvatus sp. nov., isolated from the hindgut of the termite Reticulitermes flavipes. - Leadbetter, J R (1996)
Two morphologically distinct, H2- and CO2-utilizing methanogens were isolated from gut homogenates of the subterranean termite, Reticulitermes-flavipes (Kollar) (Rhinotermitidae). Strain RFM-1 was a short straight rod (0.4 by 1.2 micron), whereas strain RFM-2 was a slightly curved rod (0.34 by 1.6 microns) that possessed polar fibers. Their morphology, gram-positive staining reaction, resistance to cell lysis by chemical agents, and narrow range of utilizable substracts were typical of species belonging to the family Methanobacteriaceae. Analysis of the nearly complete sequences of the small-subunit rRNA-encoding genes confirmed this affiliation and supported their recognition as new species of Methanobrevibacter: M. cuticularis (RFM-1) and M. curvatus (RFM-2). The per cell rates of methanogenesis by strains RFM-1 and RFM-2 in vitro, taken together with their in situ population densities (ca. 10(6) cells.gut-1; equivalent to 10(9) cells . ml of gut fluid-1), could fully account for the rate of methane emission by the live termites. UV epifluorescence and electron microscopy confirmed that RFM-1- and RFM-2-type cells were the dominant methanogens in R.flavipes collected in Michigan (but were not the only methanogens associated with this species) and that they colonized the peripheral, microoxic region of the hindgut, i.e., residing on or near the hindgut epithelium and also attached to filamentous prokaryotes associated with the gut wall. An examination of their oxygen tolerance revealed that both strains possessed catalase-like activity. Moreover, when dispersed in tubes or agar medium under H2-CO2-O2 (75: 18.8:6.2, vol/vol/vol), both strains grew to form a thin plate about 6 mm below the meniscus, just beneath the oxic-anoxic interface. Such growth plates were capable of mediating a net consumption of O2 that otherwise penetrated much deeper into uninoculated control tubes. Similar results were obtained with an authentic strain of Methanobrevibacter arboriphilicus. This is the first detailed description of an important and often cited but poorly understood component of the termite gut microbiota.